Stretched lignin/polyacrylonitrile blended carbon nanofiber as high conductive electrode in electric double layer capacitor. (1st June 2022) - Kumar, Manish; Taira, Shogo; Pakkang, Nutthira; Shigetomi, Kengo; Uraki, Yasumitsu
Abstract: In this study, lignin-based conducting carbon nanofiber mat was prepared by electrospinning followed by a thermal treatment. Lignin is a sustainable carbon precursor. Polyacrylonitrile (PAN) acts as a binder polymer, which increases the viscosity of the lignin solution using dimethylformamide solvent and helps in the formation of a stable nanofiber. The mixture solution was electrospun, followed by stabilisation and carbonisation to yield carbon nanofibers (CNFs). A fixed amount of external load was provided to the lignin fiber mat during the stabilisation procedure and then carbonised to yield stretched carbon nanofibers (S-CNFs). On stretching the mat, surface conductivity was enhanced by 3 times, and the surface area by 1.3 times compared to that of non-stretched CNFs. Finally, the electric double layer capacitor (EDLC) was assembled with the resulting (CNFs and S-CNFs) nanofiber mat using 6 M of KOH aqueous solution. S-CNFs mat exhibits a specific capacitance of 266 F g −1, which was higher than that of CNFs, i.e. 258 F g −1 at a scan rate of 5 mVs −1 .